Magnetically recoverable pyrrhotite / lignin-based biochar nano composite material as well as preparation method and application of magnetically recoverable pyrrhotite / lignin-based biochar nano composite material
Prepare magnetic pyrone ore/woody -based carbon nano -composite materials through wet mechanical chemical synthesis process, solve problems such as catalyst preparation of catalysts in existing technology and high temperature and oxygen limit in biocham technology, and achieve high -efficiency catalytic oxidation and degradation organic. The effect of pollutants has high stability and magnetic recovery performance.
Patent Information
- Application Number
- CN202411503250.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-01-28
AI Technical Summary
In the prior art, when preparing non-stoichiometric iron sulfide (Fe1-XS) catalysts, there are problems such as complex reaction conditions, high equipment requirements, high preparation price, difficult to control particle size and purity, and difficult to flexibly regulate material performance. At the same time, traditional biochar preparation processes have problems such as high temperature, oxygen limit, long time, easy generation of volatile secondary pollutants and unstable purity, which limit the performance and application of the material.
Use wet mechanical chemical synthesis process to achieve the physical hybrid and chemical synthesis reactions of iron powder, sulfur and lignin, and optimize the crystal structure and purity of composite materials through follow -up thermal treatment to prepare magnetic piacine ore/lignin -based carbon nano composite Materials (Fe1-XS/L-BC). This method does not need to add protective gas, simple operation, low energy consumption, and no secondary pollution, and it is easy to produce large -scale industrialized production.
The nano -level structure preparation of magnetic pyroneite/lignin -based carbon nano -composite material is achieved, which improves the surface area and response activity, and enhance the catalytic performance. This material has high PMS catalytic activity in the wide pH range, excellent oxidation degradation performance, and shows efficient removal of typical organic pollutants in the water body environment, and has high stability and magnetic recovery performance.
Smart Images

Figure CN119368200A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of catalytic material preparation, and specifically relates to a magnetically recoverable pyrrhotite / lignin-based biochar nanocomposite material and a preparation method and application thereof. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not be necessarily regarded as an admission or any form of suggestion that the information constitutes the prior art already known to those skilled in the art.
[0003] Peroxymonosulfate (PMS)-based advanced oxidation processes (PMSAOPs) have strong oxidation capacity and high stability and are currently one of the important processes for remediation of organic pollutants. PMS can be activated by heat, ultrasound, ultraviolet light, alkaline substances or catalysts to form various reactive oxygen species (ROS), such as sulfate (SO4· - ), hydroxyl (·OH) and superoxide (·O2 - ) Free radicals, singlet oxygen ( 1 In addition to traditional activation methods, PMS activation can also be achieved by new methods such as photothermal and piezoelectric. Among various activation methods, solid-phase catalyst activation has the advantages of mild operating conditions, no need for additional energy input, and easy catalyst recovery, and has outstanding application potential.
[0004] Non-stoichiometric iron sulfide (Fe 1-X S) is considered to be a promising PMS activator for the following reasons: (1) Fe 1-x The low release of iron ions in S can prevent reactive oxygen species (ROS) from being quenched by it; (2) The electron-rich binding state ≡ S 2- The presence of Fe 3+ Fe 2+ cycle, providing sufficient Fe for subsequent activation reactions 2+ , thus producing abundant SO4· - ; (3) Fe 1-X The significant magnetic response of S enables it to be easily separated from the solution system, simplifying its recovery and reuse. 1-X The preparation methods of S mainly include chemical coprecipitation, hydrothermal / solvothermal method, solid phase method, electrochemical method, thermal decomposition method, gas-solid reaction method and microwave-assisted synthesis method. However, these methods have the problems of complex reaction conditions, high equipment requirements, high preparation price, difficulty in controlling the particle size and purity of the obtained samples, and difficulty in achieving flexible regulation of material properties.
[0005] Lignin is one of the main components of lignocellulosic biomass and is widely present in plant cell walls. As one of the most abundant aromatic biopolymers in nature, it accounts for about 30% of the biomass generated annually worldwide. Due to its complex structure and rich aromatic rings and oxygen-containing functional groups, lignin is mostly regarded as waste or low-value fuel in traditional industries, but its chemical potential makes it an ideal raw material for high-value utilization. Lignin-based biochar (L-BC) exhibits excellent physicochemical properties due to its high carbon content, complex aromatic ring structure, rich porosity and surface active functional groups. Compared with ordinary biomass biochar (BC), lignin-based biochar has higher chemical stability and carbon fixation capacity, and the richer pore structure brings better adsorption performance, especially in the adsorption of heavy metals and organic pollutants. In addition, its good electrochemical properties make it have greater potential in energy storage and electrode material applications. Therefore, lignin-based biochar has broad application prospects in environmental remediation, pollution control and energy storage. However, problems such as high temperature, oxygen limitation, long time, easy generation of volatile secondary pollutants during the preparation process, and unstable purity of biochar products in the traditional biochar preparation process greatly restrict the performance and application of the material.
[0006] Therefore, a novel pyrrhotite / lignin-based biochar composite material (Fe 1-x S / L-BC) and is of great significance for treating pollutants in advanced oxidation systems. Summary of the invention
[0007] In order to solve the deficiencies of the prior art, the present invention aims to provide a pyrrhotite / lignin-based biochar nanocomposite material (Fe 1-x S / L-BC) and its preparation method and application. The preparation method uses a wet mechanochemical synthesis process to achieve full physical mixing and chemical synthesis reaction of iron powder, sulfur powder and lignin raw materials in one step, and optimizes the crystal structure and purity of the composite material through a subsequent heat treatment process. The mechanochemical reaction process does not require the addition of protective gas, the overall preparation process is simple to operate, has low energy consumption, does not generate secondary pollution, and is easy to achieve large-scale industrial production. The present invention also provides Fe prepared by the above preparation method 1-x Application of S / L-BC nanocomposite catalyst in catalytic oxidation degradation of organic pollutants. The catalyst has high PMS catalytic activity under a wide pH range (pH = 3 to 11), exhibits excellent oxidation degradation removal performance for typical organic pollutants in water environments, and has high stability in use and magnetic recovery performance.
[0008] In order to achieve the above object, the technical solution of the present invention is:
[0009] In a first aspect, the present invention provides a pyrrhotite / lignin-based biochar nanocomposite material comprising Fe 1-x S and lignin-based biochar, of which: Fe 1-x S is the main magnetic crystal phase, and the material is Fe 1-x Fe-S, Fe-C, CS and CS-Fe chemical bonds are formed between S and lignin-based biochar; 1-x The S nanoparticles were uniformly dispersed in the lignin-based biochar and coated by the lignin-based biochar.
[0010] The pyrrhotite / lignin-based biochar nanocomposite material provided by the present invention is a strong magnetic nanoscale material, and its magnetic material is not only from Fe 1-x S, due to Fe 1-x Due to the sufficient physical mixing and chemical bonding of S and lignin-based biochar (Fe-SC), the nanocomposite material as a whole exhibits strong magnetism, so it can be effectively reused through magnetic recovery when used.
[0011] Furthermore, the average particle size of the pyrrhotite / lignin-based biochar nanocomposite material is 100-500 nm, preferably 300 nm.
[0012] Furthermore, the lignin-based biochar raw material is one or more of enzymatic lignin, solvent lignin, alkali lignin, and sulfate lignin.
[0013] Furthermore, the mass ratio of iron powder, sulfur powder and lignin-based biochar raw material is (3-15):(5-20):(1-5), preferably (7-14):(8-16):(1-3), and further preferably (7-8):(8-10):(1-3).
[0014] In a second aspect, the present invention provides a method for preparing the above-mentioned pyrrhotite / lignin-based biochar nanocomposite material, comprising the following steps:
[0015] A composite material precursor is prepared by direct mechanochemical synthesis using iron powder, sulfur powder and lignin as raw materials and adding a wet grinding aid. The composite material precursor is subjected to heat treatment to obtain Fe 1-x S / L-BC composite nanomaterial is a pyrrhotite / lignin-based biochar nanocomposite material.
[0016] Furthermore, the steps of the direct mechanochemical synthesis method are: using iron powder, sulfur powder and lignin as raw materials, adding a wet grinding aid for mechanical ball milling, washing, separating and drying to obtain a composite material precursor.
[0017] The overall preparation method of the present invention is divided into two steps:
[0018] The first step is direct mechanochemical synthesis: iron powder, sulfur powder and lignin are directly subjected to mechanical ball milling. During this process, Fe 1-x S, on the other hand, lignin directly generates lignin-based biochar precursors through direct mechanochemical reactions and chemical reactions with iron powder / sulfur powder. The direct mechanochemical synthesis process effectively reduces the synthesis temperature of lignin-based biochar, reduces the overall energy consumption, and the one-step synthesis avoids the high-temperature oxygen-limited pyrolysis, acidification, washing, drying and other steps in the pre-preparation of biochar, simplifying the process.
[0019] The second step is the heat treatment process of the composite material: the composite material obtained in the first step is heat treated to remove impurities such as sulfur powder in the composite material, and further optimize and adjust the crystal form and crystallinity of the composite material.
[0020] Furthermore, the particle size of the iron powder is ≤100 mesh (no special requirement for purity). There is no special requirement for the particle size and purity of the sulfur powder.
[0021] Furthermore, the lignin-based biochar raw material is one or more of enzymatic lignin, solvent lignin, alkali lignin, and sulfate lignin, and alkali lignin is further preferred. The extraction process of alkali lignin is simple and the cost is low.
[0022] The advantages of directly using various lignins to prepare lignin-based biochar are: on the one hand, as one of the main components of lignocellulosic biomass, lignin is free from the interference of impurities such as Si / Na / Ca / K in raw materials such as bamboo powder, straw, and sawdust, and the prepared material has higher purity; on the other hand, lignin has a complex structure and contains rich aromatic rings and oxygen-containing functional groups. Therefore, the lignin-based biochar prepared from it shows better physical and chemical properties than ordinary biochar due to its high carbon content, complex aromatic ring structure, rich porosity and surface active functional groups.
[0023] Furthermore, the mass ratio of iron powder, sulfur powder and lignin-based biochar raw material is (3-15):(5-20):(1-5), preferably (7-14):(8-16):(1-3), and further preferably (7-8):(8-10):(1-3).
[0024] Furthermore, the wet grinding aid is one or more of ethanol, ethylene glycol and methanol, preferably ethanol.
[0025] The amount of the wet grinding aid is 0.2-2 mL / g of the mixed material, preferably 1-1.5 mL / g.
[0026] Furthermore, the ball milling adopts a planetary ball mill, and in the mechanical ball milling, the rotation speed is 300-600r / min, and the ball milling time is 24-72h.
[0027] The ball mill jar and the grinding balls are made of zirconium oxide, and the mass ratio of the grinding balls to the mixed material is (10-60):1, preferably (10-20):1.
[0028] Furthermore, the washing is carried out by sequentially using water and ethanol; the separation is carried out by centrifugal separation or filtration separation; and the drying is carried out by vacuum drying.
[0029] Furthermore, the heat treatment is carried out under a protective atmosphere, which is one or more of nitrogen, argon, and helium, with a gas flow rate of 0.2 to 2 L / min.
[0030] The heat treatment temperature is 300-700°C, preferably 500-600°C, the calcination time is 1-8h, preferably 2-3h, the heating rate is 3-15°C / min, and the cooling rate is cooling with the furnace.
[0031] In a third aspect, the present invention provides the use of the above-mentioned pyrrhotite / lignin-based biochar nanocomposite material in catalytic oxidation degradation of pollutants. When the pyrrhotite / lignin-based biochar nanocomposite catalyst is used for catalytic oxidation degradation of organic pollutants, the operation is simple, the degradation rate is high, the performance is stable, and the magnetic recovery and reuse can be performed.
[0032] Furthermore, the pollutants include one or more of organic dyes, antibiotics and industrial pollutants.
[0033] The organic dye includes methylene blue.
[0034] The antibiotics include sulfadiazine, tetracycline hydrochloride, and sulfamethoxazole.
[0035] The industrial pollutants include bisphenol A (bisphenol A).
[0036] In a fourth aspect, the present invention provides a method for catalytic oxidation degradation of pollutants using the above-mentioned pyrrhotite / lignin-based biochar nanocomposite material, comprising the following steps:
[0037] The pyrrhotite / lignin-based biochar nanocomposite material is directly contacted with the pollutant, and then peroxymonosulfate is added.
[0038] That is, the pyrrhotite / lignin-based biochar nanocomposite material is directly put into water containing pollutants, and then peroxymonosulfate is added.
[0039] Furthermore, the addition amount of the pyrrhotite / lignin-based biochar nanocomposite material is 0.2-0.9 g / L, preferably 0.2-0.3 g / L.
[0040] Furthermore, the amount of peroxymonosulfate added is 0.3 to 1 mM, preferably 0.3 to 0.6 mM.
[0041] Furthermore, the pH of the water containing pollutants is 3 to 11. The pollutant removal rate is fast and the pH application range is wide.
[0042] Furthermore, when the pollutant to be treated is bisphenol A (diphenol propane), the concentration of bisphenol A (diphenol propane) is 10 to 50 mg / L, preferably 10 to 20 mg / L.
[0043] Furthermore, when the pollutant to be treated is sulfadiazine, the concentration of sulfadiazine is 10-50 mg / L, preferably 10-30 mg / L.
[0044] Furthermore, when the pollutant to be treated is methylene blue, the concentration of sulfadiazine is 10-150 mg / L, preferably 50-100 mg / L.
[0045] The beneficial effects of the present invention are:
[0046] (1) The nanostructure of pyrrhotite / lignin-based biochar nanocomposites was successfully prepared by synergistic heat treatment of iron powder, sulfur powder and lignin using a wet mechanochemical process, which further improved its specific surface area and reaction activity and enhanced its catalytic performance. 1-x The S bonds form pyrrhotite, making the pyrrhotite / lignin-based biochar nanocomposites magnetically recyclable.
[0047] (2) The preparation method adopts a wet mechanochemical process, which achieves the physical mixing and chemical reaction of iron powder, sulfur powder and lignin in one step by transferring and converting mechanical energy into chemical energy. No protective gas is required in the process, which simplifies the operation steps and reduces the process complexity. The entire preparation process has low energy consumption and avoids the generation of harmful by-products, ensuring environmental protection and complying with the principles of green chemistry.
[0048] (3) During the preparation process, sulfur not only reacts with iron to form Fe 1-x S also modified the biochar surface to generate CS bonds, which further bonded with Fe 1-x The combination of S increases the ability of the composite material to reduce Fe(III), its electrical conductivity and electron transfer capacity, thereby further improving the catalytic performance of the material. In addition, the mechanochemical reaction process causes lignin to pre-react, effectively reducing the energy required for its subsequent conversion into biochar.
[0049] (4) The rich C=O and OC=O in lignin-based biochar increases the electron density around Fe atoms, promotes the formation of unpaired electrons and the transfer of electrons in the catalyst, and increases the Fe 1-xExcellent performance of the S / L-BC system. The persistent free radicals (PFRs) in lignin-based biochar promote the generation of reactive oxygen species by participating in redox reactions, reducing the residence time of pollutants, thereby shortening the water treatment cycle and significantly improving the efficiency of the entire water treatment process.
[0050] (5) During the preparation process, the two components of lignin-based biochar and pyrrhotite are fully mixed and generated in situ, which enables the effective coating of pyrrhotite by biochar, improves the stability of the catalyst, and effectively reduces the dissolution of ions in the material, avoiding the secondary pollution problem that is prone to occur in conventional catalytic systems.
[0051] (6) The heat treatment process during the preparation process further optimizes the crystal structure and purity of the composite material, improves the stability and performance of the catalyst, extends its service life, reduces the frequency of replacement, and thus reduces maintenance and operating costs.
[0052] (7) The realization of the nanostructure of the composite material greatly increases the specific surface area of the material, improves the reaction rate and catalytic efficiency, and ultimately improves the treatment effect. It is particularly suitable for the efficient treatment of difficult-to-degrade organic pollutants, such as organic dyes such as methylene blue, antibiotics such as sulfadiazine, tetracycline hydrochloride and sulfamethoxazole, and industrial pollutants such as bisphenol A (bisphenol propane), which improves the depth and thoroughness of pollutant treatment. Composite catalysts significantly improve the degradation efficiency of organic pollutants, especially in water pollution control, which can greatly reduce treatment time and treatment costs, and effectively improve the efficiency of wastewater purification.
[0053] (8) The composite catalyst maintains high catalytic reaction activity within a wide pH range (3-11), adapts to different water quality conditions, expands its scope of application in actual water treatment applications, and improves the stability and reliability of the treatment effect.
[0054] (9) The long-term stable catalytic activity of the composite material extends the effective use time of the material, reduces the operational burden and resource waste caused by frequent catalyst replacement, and improves economic benefits.
[0055] (10) The catalyst can be recovered and reused through magnetic recovery, which is simple to operate and saves resources, reducing catalyst consumption and waste disposal costs, further improving economy and sustainability. BRIEF DESCRIPTION OF THE DRAWINGS
[0056] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0057] Figure 1 The Fe prepared in Example 1 of the present invention 1-xXRD patterns of S / L-BC nanocomposites;
[0058] Figure 2 The Fe prepared in Example 1 of the present invention 1-x Field emission scanning electron microscopy (FESEM) images of S / L-BC nanocomposites;
[0059] Figure 3 The Fe prepared in Example 1 of the present invention 1-x XPS spectra of S / L-BC nanocomposites;
[0060] Figure 4 The Fe prepared in Example 2 of the present invention 1-x XRD patterns of S / L-BC nanocomposites;
[0061] Figure 5 The Fe 1-x Degradation rate diagram of BPA in organic wastewater by S / L-BC nanocomposite;
[0062] Figure 6 is Fe in Example 1 of the present invention 1-x S / L-BC nanocomposite, Fe+S+L-BC physical composite in Comparative Example 1, Fe 1-x Comparison of the BPA degradation performance of L-BC in S material comparative example 3 and FeS2 / BC nanocomposite materials in comparative example 4;
[0063] Figure 7 is Fe in Example 1 of the present invention 1-x S / L-BC nanocomposite, Fe+S+L-BC physical composite in Comparative Example 1, Fe 1-x Comparison chart of TOC removal performance of S materials for pollutants;
[0064] Figure 8 The Fe used in Application Example 2 of the present invention 1-x Actual picture of magnetic recovery of S / L-BC nanocomposite;
[0065] Fig. 9 The Fe in Application Example 2 of the present invention 1-x Results of the S / L-BC repeated use experiment (15-min degradation rate of BPA). DETAILED DESCRIPTION
[0066] Explanation of terms involved:
[0067] Fe 1-xS: pyrrhotite; L-BC: lignin-biochar, BPA: bisphenol A (bisphenol propane); SDZ: sulfadiazine, PMS: peroxymonosulfate; MB: methylene blue, SO4· - : Sulfate free radical.
[0068] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.
[0069] Example 1
[0070] A method for preparing a pyrrhotite / lignin-based biochar nanocomposite material, comprising:
[0071] Step 1: 12 g of a mixture of iron powder, sulfur powder and lignin weighed in a mass ratio of 7:8:1 was placed in a zirconia ball mill, and 240 g of zirconia balls and 12 mL of ethanol were added thereto. A planetary ball mill was set to 400 r / min and operated for 72 h.
[0072] Step 2: After the ball mill is finished and cooled to room temperature, rinse the ball mill with water and transfer the mixture in the ball mill to a beaker. After stirring evenly, transfer the mixed liquid to a centrifuge tube and centrifuge at 1000 rpm for 10 minutes. The obtained solid material is washed and centrifuged three times with water and ethanol in turn, and then placed in a freeze dryer for 24 hours;
[0073] Step 3: The mixed material obtained in step 2 was transferred to a vacuum tube furnace, argon was used as the protective gas (gas flow rate was 1.5 L / min), the heating rate was controlled to be 10°C / min, the calcination temperature was 600°C, and the calcination time was 2 h to prepare Fe 1-x S / L-BC nanocomposites.
[0074] Example 1 Fe 1-x The XRD patterns of S / L-BC nanocomposites are shown in Figure 1 ,Depend on Figure 1 It can be seen that the synthesis of Fe 1-x The characteristic diffraction peaks of S / L-BC nanocomposites are basically consistent with the standard card of pyrrhotite (JCPDS: 29-0726), and no other impurity peaks such as elemental iron and elemental sulfur are observed, indicating that this method successfully prepared high-purity Fe 1-x S / L-BC composite material.Fe 1-x The main diffraction peaks of S / L-BC are sharp, indicating that the synthesized Fe 1-x S / L-BC material has good crystallinity.
[0075] Example 1 Fe 1-x The FESEM images of S / L-BC nanocomposites are shown in Figure 2 ,Depend on Figure 2 It can be seen that the Fe and S elements in the composite material are uniformly doped in C, and the in-situ generation of the two components of lignin-based biochar and pyrrhotite is fully mixed. In addition, the biochar is effectively coated on pyrrhotite, and the biochar and Fe 1-x The S nanoparticles are mixed evenly, the sample has small agglomeration and presents a regular morphology.
[0076] Example 1 Fe 1-x XPS graph of S / L-BC nanocomposite is shown in Figure 3 ,Depend on Figure 3 It can be seen that the mutual reaction between the elements was achieved during the co-milling reaction of iron powder, sulfur powder and lignin, except for Fe 1-x In addition to the basic chemical bonds (Fe-S, CC) between sulfur and biochar, the co-generated Fe-C and CS bonds indicate that sulfur, in addition to combining with iron to form Fe 1-x In addition to S, the biochar surface was also modified to generate CS, which can be further combined with Fe through CS-Fe 1-x S is combined to ensure the stability of the material. The ability of the composite material to reduce Fe(III), its electrical conductivity and electron transfer ability are increased, thereby further improving the catalytic performance of the material.
[0077] Example 2
[0078] A method for preparing a pyrrhotite / lignin-based biochar nanocomposite material, comprising:
[0079] Step 1: 12 g of a mixture of iron powder, sulfur powder and lignin weighed in a mass ratio of 14:16:3 was placed in a zirconia ball mill, and 240 g of zirconia balls and 12 mL of ethanol were added thereto. A planetary ball mill was used with the parameters set at 400 r / min and operated for 72 h.
[0080] Step 2: After the ball mill is finished and cooled to room temperature, rinse the ball mill with water and transfer the mixture in the ball mill to a beaker. After stirring evenly, transfer the mixed liquid to a centrifuge tube and centrifuge at 1000 rpm for 10 minutes. The obtained solid material is washed and centrifuged three times with water and ethanol in turn, and then placed in a freeze dryer for 24 hours;
[0081] Step 3: The mixed material obtained in step 2 was transferred to a vacuum tube furnace, argon was used as the protective gas (gas flow rate was 1.5 L / min), the heating rate was controlled to be 10°C / min, the calcination temperature was 500°C, and the calcination time was 3 h to prepare Fe 1-xS / L-BC nanocomposite material. Fe prepared in Example 2 1-x The XRD patterns of S / L-BC nanocomposites are shown in Figure 4 ,Depend on Figure 4 It can be seen that the Fe synthesized by changing the raw material ratio and preparation conditions 1-x The characteristic diffraction peaks of S / L-BC nanocomposites are consistent with those of pyrrhotite, and no other impurity peaks such as elemental iron and elemental sulfur are observed, indicating that this method can prepare high-purity Fe within a certain parameter range. 1-x S / L-BC composite material.
[0082] Comparative Example 1
[0083] The method for preparing the Fe+S+L-BC physical composite material is different from that in Example 1 in that the physical composite material is directly heat treated without wet ball milling.
[0084] 12g of the mixture consisting of iron powder, sulfur powder and lignin was placed in an agate mortar and ground for 30min until the mixture was uniform. The mixture was transferred to a vacuum tube furnace, the heating rate was controlled to be 10℃ / min, the calcination temperature was 600℃, the calcination time was 2h, argon was used as the protective gas, and the protective gas flow rate was 1.5L / min, and the Fe+S+L-BC physical composite material was prepared by pyrolysis.
[0085] Comparative Example 2
[0086] Fe 1-x The preparation method of S is different from that of Example 1 in that only iron powder and sulfur powder are used as raw materials, and the remaining steps are the same:
[0087] Step 1: Weigh 12g of the mixture of iron powder and sulfur powder according to the mass ratio of 7:8 and place it in a zirconia ball mill, and add 240g of zirconia balls and 12mL of ethanol. Use a planetary ball mill with the parameters set at 400r / min and run for 72h.
[0088] Step 2: After the ball mill is finished and cooled to room temperature, rinse the ball mill with water and transfer the mixture in the ball mill to a beaker. After stirring evenly, transfer the mixed liquid to a centrifuge tube and centrifuge at 1000 rpm for 10 minutes. The obtained solid material is washed and centrifuged three times with water and ethanol in turn, and then placed in a freeze dryer for 24 hours;
[0089] Step 3: The mixed material obtained in step 2 was transferred to a vacuum tube furnace, argon was used as the protective gas (gas flow rate was 1.5 L / min), the heating rate was controlled to be 10°C / min, the calcination temperature was 600°C, and the calcination time was 2 h to prepare Fe 1-x S material.
[0090] Comparative Example 3
[0091] The preparation method of L-BC is different from that of Example 1 in that the material only uses lignin as raw material, does not undergo wet ball milling, and only undergoes heat treatment.
[0092] 12 g of lignin was placed in a vacuum tube furnace, the heating rate was controlled to be 10°C / min, the calcination temperature was 600°C, the calcination time was 2 h, argon was used as the protective gas, the protective gas flow rate was 1.5 L / min, and pyrolysis was performed to prepare L-BC material.
[0093] Comparative Example 4
[0094] (1) The biomass raw material (bamboo charcoal) was placed in a vacuum tube furnace, the heating rate was controlled to be 10°C / min, the calcination temperature was 700°C, the calcination time was 2h, argon was used as the protective gas, and the protective gas flow rate was 400mL / min, and the biochar material was prepared by pyrolysis. The obtained sample was placed in 68% (wt%) concentrated nitric acid for acidification, the acidification temperature was 60°C, and the acidification time was 2h. After acidification, the biochar powder material was obtained by washing with distilled water until neutral, filtering and drying.
[0095] (2) Iron powder, sulfur powder and the biochar powder prepared in step (1) are mixed (wherein the molar ratio of Fe:S is 1:2.1, and the mass ratio of iron powder to biochar is 7:1), and the mixed material and dry grinding aid Na2S are added to a planetary high-energy ball mill at a mass ratio of 20:1, with a steel ball diameter of 5 mm and a ball-to-material ratio of 30:1, and then wet grinding aid ethanol is added for ball milling, the ball milling speed is 400r / min; the ball milling time is 48h. After the ball milling is completed, oxygen-free water and anhydrous ethanol are used to wash and collect the ball milling product in turn under the protection of inert gas, the product is collected by centrifugation, and then dried, and dried at 80°C for 30h under the protection of inert gas, and FeS2 / BC nanocomposite materials are obtained after drying.
[0096] Application Example 1
[0097] Fe 1-x Removal of BPA from water by S / L-BC nanocomposites.
[0098] At room temperature, a BPA solution with a concentration of 20 mg / L was prepared to simulate organic wastewater. The initial pH of the solution was adjusted to 3, 5, 7, 9, and 11 using NaOH and HCl, and the Fe prepared in Example 1 was added to the organic wastewater in sequence. 1- xAfter the S / L-BC nanocomposite material (catalyst dosage 0.3 g / L) reached adsorption-desorption equilibrium (30 min), 0.6 mM PMS was added and stirred for continuous reaction. The BPA concentration corresponding to different reaction times was determined by high performance liquid chromatography (HPLC) and the degradation rate of BPA was calculated. 1-x The degradation rate of BPA in organic wastewater by S / L-BC nanocomposite is shown in the figure Figure 5 ,Depend on Figure 5 It can be seen that the Fe prepared by the present invention 1-x S / L-BC nanocomposites maintain excellent degradation performance in a wide pH range.
[0099] Application Example 2
[0100] Using the Fe prepared in Example 1 1-x S / L-BC nanocomposite, Fe+S+L-BC physical composite in Comparative Example 1, Fe 1-x The S material, L-BC in comparative example 3, and FeS2 / BC nanocomposite material (Fenton system) in comparative example 4 degrade BPA in organic wastewater. As a comparative experiment, a single PMS was also introduced to degrade pollutants. The pH of this system was 5.56.
[0101] At room temperature, a 20 mg / L BPA solution was prepared to simulate organic wastewater, which was divided into five equal parts. The Fe prepared in Example 1 was added to the organic wastewater solution. 1-x S / L-BC nanocomposite material (catalyst dosage 0.3 g / L), Fe+S+L-BC physical composite material in Comparative Example 1 (catalyst dosage 0.3 g / L), Fe 1-x S material (catalyst dosage 0.3g / L) and L-BC (catalyst dosage 0.3g / L) in Comparative Example 3, and no catalyst was added to the other part. After adsorption for 30min, 0.6mM PMS was added respectively, and the reaction was stirred continuously. The concentration of BPA corresponding to different reaction times was measured by high performance liquid chromatography (HPLC), and the degradation rate of BPA was calculated. The experimental steps for the degradation of BPA by FeS2 / BC nanocomposite material (catalyst dosage 0.3g / L) in Comparative Example 4 were the same as those in Application Example 2, except that PMS was replaced by H2O2 (1.25mM).
[0102] Use Fe 1-x S / L-BC nanocomposites, Fe+S+L-BC physical composites, Fe 1-x The comparison of BPA degradation performance of S material, L-BC and FeS2 / BC is shown in Figure 6The results show that L-BC+PMS and PMS alone have basically no degradation effect on the pollutant BPA. 1-x S+PMS, Fe+S+L-BC+PMS systems showed a slight degradation effect on pollutants, while Fe 1-x The degradation performance of the S / L-BC+PMS system is much higher than that of other materials, and BPA can be 100% removed within 15 minutes. This proves that the composite material prepared by this method has better catalytic performance.
[0103] Use Fe 1-x S / L-BC nanocomposites, Fe+S+L-BC physical composites and Fe 1-x The TOC removal performance comparison of S materials for pollutants is shown in Figure 7 The results show that Fe 1-x Compared with Fe+S+L-BC physical composites and Fe 1-x The S material showed better TOC removal.
[0104] Used Fe 1-x The actual effect of magnetic recovery of S / L-BC nanocomposite materials is shown in the figure Figure 8 The results show that the use of external magnets can 1-x The S / L-BC nanocomposite material was adsorbed on one side of the container, making the liquid clear. This indicates that the catalyst has good magnetic recovery performance and can be effectively separated and recovered by the magnetic field, thus achieving catalyst reuse, reducing material loss and operating costs, while maintaining the water purification effect.
[0105] Fe 1-x The results of the S / L-BC repeated use experiment are as follows Fig. 9 As shown in Figure 1 (15 min degradation rate of BPA). The results show that even after multiple cycles, the degradation rate of BPA is still very high. This verifies that Fe 1-x The long-term stability of the catalytic activity of the S / L-BC composite material extends the effective use time of the material.
[0106] Application Example 3
[0107] Fe 1-x Removal of sulfadiazine (SDZ) from water by S / L-BC nanocomposites.
[0108] At room temperature, a 30 mg / L SDZ solution was prepared to simulate organic wastewater. The Fe prepared in Example 1 was added to the organic wastewater. 1-xAfter the S / L-BC nanocomposite (catalyst dosage 0.3 g / L) reached adsorption-desorption equilibrium (30 min), 0.6 mM PMS was added and stirred for continuous reaction. The SDZ concentration corresponding to different reaction times was determined by high performance liquid chromatography (HPLC) to calculate the degradation rate of SDZ.
[0109] Application Example 4
[0110] What is different from Application Example 3 is that the pollutants in the water body to be removed are different.
[0111] In this application example, Fe is prepared in Example 1. 1-x The S / L-BC nanocomposite material removes methylene blue from water, wherein the concentration of methylene blue is 100 mg / L, and the remaining steps are the same as those in Application Example 2. The specific degradation rates are shown in Table 1.
[0112] Table 1
[0113]
[0114]
[0115] It can be seen from Table 1 that Fe 1-x The degradation rates of SDZ, BPA and methylene blue by S / L-BC nanocomposites reached 100% at 1 min, 15 min and 3 min, respectively, indicating that Fe 1-x Performance advantages of S / L-BC nanocomposites.
[0116] The Fe prepared by the present invention 1-x The S / L-BC-based persulfate system showed excellent degradation performance for representative pollutants, and in terms of BPA degradation, it was significantly better than the currently reported related BPA degradation literature, as shown in Table 2 below.
[0117] Table 2
[0118]
[0119]
[0120] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A pyrrhotite / lignin-based biochar nanocomposite material, characterized in that: The material contains Fe 1-x S and lignin-based biochar, of which: Fe 1-x S is the main magnetic crystal phase, and the material is Fe 1-x Fe-S, Fe-C, CS and CS-Fe chemical bonds are formed between S and lignin-based biochar; 1-x The S nanoparticles were uniformly dispersed in the lignin-based biochar and coated by the lignin-based biochar.
2. The pyrrhotite / lignin-based biochar nanocomposite material according to claim 1, characterized in that: The average particle size of the pyrrhotite / lignin-based biochar nanocomposite material is 100-500 nm; Or, the lignin-based biochar raw material is one or more of enzymatic lignin, solvent lignin, alkali lignin, and kraft lignin; Or, the mass ratio of iron powder, sulfur powder and lignin-based biochar raw material is (3-15):(5-20):(1-5), preferably (7-14):(8-16):(1-3).
3. The method for preparing the pyrrhotite / lignin-based biochar nanocomposite material according to claim 1 or 2, characterized in that: The method comprises the following steps: using iron powder, sulfur powder and lignin as raw materials, adding a wet grinding aid, adopting a direct mechanochemical synthesis method to prepare a composite material precursor, and subjecting the composite material precursor to a heat treatment to obtain Fe 1-x S / L-BC composite nanomaterial is a pyrrhotite / lignin-based biochar nanocomposite material.
4. The preparation method according to claim 3, characterized in that: The direct mechanochemical synthesis method comprises the following steps: using iron powder, sulfur powder and lignin as raw materials, adding a wet grinding aid for mechanical ball milling, washing, separating and drying to obtain a composite material precursor; Or, the lignin-based biochar raw material is one or more of enzymatic lignin, solvent lignin, alkali lignin, and kraft lignin; Or, the mass ratio of iron powder, sulfur powder and lignin-based biochar raw material is (3-15):(5-20):(1-5), preferably (7-14):(8-16):(1-3); Or, the washing is carried out using water and ethanol in sequence; Or, in the mechanical ball milling, the rotation speed is 300-600 r / min, and the ball milling time is 24-72 h; The mass ratio of grinding balls to mixed materials is (10-60):
1.
5. The preparation method according to claim 3 or 4, characterized in that: The wet grinding aid is one or more of ethanol, ethylene glycol and methanol; The dosage of the wet grinding aid is 0.2-2 mL / g of the mixed material.
6. The preparation method according to claim 3, characterized in that: The heat treatment is carried out under a protective atmosphere, wherein the protective atmosphere is one or more of nitrogen, argon, and helium, and the gas flow rate is 0.2 to 2 L / min; Alternatively, the heat treatment temperature is 300-700° C., preferably 500-600° C., the calcination time is 1-8 hours, preferably 1-3 hours, and the heating rate is 3-15° C. / min.
7. Use of the pyrrhotite / lignin-based biochar nanocomposite material according to claim 1 or 2 or the pyrrhotite / lignin-based biochar nanocomposite material obtained by the preparation method according to any one of claims 3 to 6 in catalytic oxidation degradation of pollutants.
8. The use according to claim 7, characterized in that: The pollutants include one or more of organic dyes, antibiotics and industrial pollutants; Preferably, the organic dye comprises methylene blue; Preferably, the antibiotics include sulfadiazine, tetracycline hydrochloride, and sulfamethoxazole; Preferably, the industrial pollutant comprises bisphenol A (bisphenol A).
9. A method for catalytic oxidation degradation of pollutants using pyrrhotite / lignin-based biochar nanocomposite materials, characterized in that: The steps include: The pyrrhotite / lignin-based biochar nanocomposite material according to claim 1 or 2 is directly contacted with pollutants, and then peroxymonosulfate is added.
10. The method according to claim 9, characterized in that: The addition amount of the pyrrhotite / lignin-based biochar nanocomposite material is 0.2 to 0.9 g / L; Alternatively, the amount of permonosulfate added is 0.3 to 1 mM; Or, the pH of the water containing the pollutant is 3-11.
Citation Information
Cited By
Magnetic FeS2 / biochar material for activating peracetic acid to degrade antibiotics and preparation method of magnetic FeS2 / biochar material
CN120132875A